SYNTHESIS AND CHARACTERIZATION OF (WO3 )n VIA SOL-GEL FILMS USING DIP COATING TECHNIQUE - Morales Gomero, Juan C. (2017)
In the present investigation (WO3 )n films were synthesized by Sol-Gel methodology by dip coating techniques using Na2 WO4 as precursor salt to form polytungstic acid ((WO3 )n . nH2 O), which by dehydration formed the oxide (WO3 )n that was deposited in two different substrates: 316L stainless steel and FTO (Fluorine doped Tin Oxide), which were deposited under the same experimental conditions and subsequently sintered at 400 ° C for a lapse of 30 minutes in both cases. It was observed that the film of (WO3 )n deposited on steel presented a greater photocurrent generated of 133 μAcm-2, compared to 29 μAcm-2 for (WO3 )n film measured by cyclic voltammetry in a potentiostat (AUTOLAB PGSTAT302N) against the FTO-supported film. The films were characterized using Fourier Transform Infrared Spectroscopy (FTIR) techniques, using the SHIMADZU IR PRESTIGE 21 FTIR spectrophotometer to recognize W-O-W (826 cm-1) links on the surface of the FTO and W-O-W links (652 cm-1), W=O (953 cm-1), W-O (1414 cm-1) and O-H vibration (2338 cm-1) on the steel surface; Raman spectroscopy at 532 nm to confirm symmetric stretches of W-O bonds that could not be clearly identified by FTIR; X-ray diffraction (XRD) to confirm the crystalline structure of the films, finding a predominantly monoclinic structure whose base structure corresponds to WO3 , and an approximate estimate of crystallite size of 27,4 nm determined by the equation of Debye Scherrer and X-ray Dispersive Energy (EDX) for elemental analysis, yielding a centesimal composition of 77,7 % by mass of W corresponding to the empirical formula of WO3, and finally a morphological analysis by Scanning Electron Microscopy (SEM) that showed which showed the formation of layers (films) with nanostructures with non-uniform particle size ranging between 50 and 100 nm.